When Will a Consequentialist Push You in Front of a Trolley? - Woodcock, Scott (Australasian Journal of Philosophy, 2017)
As the trolley problem runs its course, consequentialists tend to adopt one of two strategies: (a) silently take comfort in the fact that deontological rivals face their own enduring difficulties, or (b) appeal to cognitive psychology to discredit the deontological intuitions on which the trolley problem depends. I refer to the first strategy assilent schadenfreudeand the second asdebunking attack. My aim in this paper is to argue that consequentialists ought to reject both strategies and instead opt for what I callrobust advantage. This strategy emphasizes the intricate calculations that consequentialists employ to defend against objections based on friendship and integrity. I argue that these calculations offer consequentialism an explanatory advantage over deontology in the context of the trolley problem. It requires striking a delicate balance between deeply internalized dispositions to avoid causing harm and a context-sensitive ability to prevent disasters; however, empirical data help consequentialism on this front by illustrating that the integration of separate cognitive functions is an ordinary part of human psychology.